2018
DOI: 10.1177/0959683618777072
|View full text |Cite
|
Sign up to set email alerts
|

UV-B-absorbing compounds in modern Cedrus atlantica pollen: The potential for a summer UV-B proxy for Northwest Africa

Abstract: Sporopollenin is a complex biopolymer which is the main component of the pollen grain exine and is partly composed of the aromatic compounds para-coumaric acid (pCA) and ferulic acid (FA). These compounds absorb ultraviolet-B radiation (UV-B, 280-315 nm), and their abundance in pollen and spores has been shown to increase in response to increased UV-B flux. Here, we show that the relative abundance of UV-B-absorbing compounds (UACs) measured using Fourier Transform Infrared Spectrometry (FTIR) in modern pollen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 86 publications
(166 reference statements)
3
23
0
Order By: Relevance
“…Further enhancements to this approach may be possible by incorporating pollen grain size or surface sculpture information into the classification procedure. As already noted, the size variation across Poaceae pollen grains broadly scales with genome size, with generally larger grains in domesticated types than in wild types (Andersen, 1979;Andersen and Bertelsen, 1972;Bennett, 1972;Beug, 1961Beug, , 2004Bottema, 1992;Firbas, 1937;Tweddle et al, 2005). If combined with chemical data, pollen grain size, along with pore and annulus size, may be useful for improving the classification of wild types and their domesticated descendants.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Further enhancements to this approach may be possible by incorporating pollen grain size or surface sculpture information into the classification procedure. As already noted, the size variation across Poaceae pollen grains broadly scales with genome size, with generally larger grains in domesticated types than in wild types (Andersen, 1979;Andersen and Bertelsen, 1972;Bennett, 1972;Beug, 1961Beug, , 2004Bottema, 1992;Firbas, 1937;Tweddle et al, 2005). If combined with chemical data, pollen grain size, along with pore and annulus size, may be useful for improving the classification of wild types and their domesticated descendants.…”
Section: Discussionmentioning
confidence: 94%
“…Attempts to distinguish among and between wild grasses and their domesticated relatives have relied on a combination of grain size and shape, pore diameter and position, annulus width and thickness, and exine structure and microsculpture (Andersen, 1979;Beug, 1961Beug, , 2004Bottema, 1992;Dickson, 1988;Firbas, 1937;Joly et al, 2007;Köhler and Lange, 1979;Rowley, 1960;Tweddle et al, 2005), although of these various characters grain size has been most commonly relied upon in routine palynological studies (Bottema, 1992). Pollen grain size varies between 30 and 100 µm among Poaceae species and broadly correlates with genome size (Bennett, 1972). Since domesticated grasses are typically polyploid they have larger pollen grains than their wild type relatives, and this has led to a size-based circumscription of a "Cerealia" type (Andersen, 1979;Beug, 1961Beug, , 2004Bottema, 1992;Firbas, 1937;Joly et al, 2007;Tweddle et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested plasticity of pollen chemistry to climate and other environmental variables (Zimmermann & Kohler, 2014;Zimmermann et al, 2017). For example, temperature has been connected to changes in protein as well as lipid content in both controlled and field experimental conditions (Lahlali et al, 2014;Zimmermann & Kohler, 2014;Jiang et al, 2015;Zimmermann et al, 2017), whilst the effects of exposure to UV-B radiation on pollen chemistry have gained increasing attention (Rozema et al, 2001;Blokker et al, 2006;Fraser et al, 2011;Willis et al, 2011;Jardine et al, 2017;Bell et al, 2018). Additionally, there may be confounding effects related to local adaptation and hybridisation.…”
Section: Prospects For Developments Using Fossil Pollenmentioning
confidence: 99%
“…Additionally, there may be confounding effects related to local adaptation and hybridisation. For example, Bell et al (2018) investigated changes in Cedrus pollen chemistry to UV-B radiation and their results suggest a heritable component in the pollen chemical response to UV-B, from analyses of FTIR spectra of pollen samples from botanic gardens closely resembling their source of origin.…”
Section: Prospects For Developments Using Fossil Pollenmentioning
confidence: 99%
See 1 more Smart Citation